2009
DOI: 10.1007/s10750-009-9851-4
|View full text |Cite
|
Sign up to set email alerts
|

Tyrrhenian basins of Ligury as a new peri-Mediterranean ichthyogeographic district? Population structure of Telestes muticellus (Osteichthyes, Cyprinidae), a primary freshwater fish

Abstract: The phylogeographic structure of vairone (Telestes muticellus), a primary freshwater fish endangered in a large part of its distributional range, was assessed: i) to reconstruct the complex dispersion pattern in the upper Tyrrhenian hydrographic basins of Ligury, actually not recognised as peri-Mediterranean ichthyogeographic district, and ii) to evidence the shape of population genetic structure as useful tool for future conservation strategies. A partial fragment of mitochondrial DNA cytochrome b (497 bp) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The existence of genetically distinct allopatric taxa at least identifies them as Evolutionary Significant Units [ 55 ], but their taxonomic rank remains undefined. Nonetheless, phylogeographic structures and genetic similarity/dissimilarity between and within territories could be a diagnostic key for the definition of ichthyogeographic (or more generally biogeographic) districts [ 56 58 ]. Therefore, AC can be split into its northern Adriatic part (NAAC) and its Tyrrhenian and southern Adriatic part (TSAAC).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of genetically distinct allopatric taxa at least identifies them as Evolutionary Significant Units [ 55 ], but their taxonomic rank remains undefined. Nonetheless, phylogeographic structures and genetic similarity/dissimilarity between and within territories could be a diagnostic key for the definition of ichthyogeographic (or more generally biogeographic) districts [ 56 58 ]. Therefore, AC can be split into its northern Adriatic part (NAAC) and its Tyrrhenian and southern Adriatic part (TSAAC).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, this eventual isolation may be recent and not enough to drive morphological diversifications. Although there is no evidence of comparative investigations on the genetic variability including the investigated species, this may be corroborated by genetic studies for the three species, showing a very low variability in R. rubilio from river basins of southern Italy (Nonnis Marzano et al 2007), and low variability in S. lucumonis from Umbria (Gigliarelli et al 2012), and in T. muticellus from eastern Ligurian basins (Zaccara & Delmastro 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Fax: +39 (0)6 57 33 63 21. Email: massimiliano.scalici@uniroma3.it Serchio river basins of the Tuscany-Latium district, therein with 10-12 subpopulations (Crivelli 2006b); Tm is restricted to northern and Central Italy, and has been introduced in Liguria (Crivelli & Bianco 2006) although Zaccara & Delmastro (2009) and Marchetto et al (2011) suggested a natural colonization of the latter region throughout the crossing of Alpine and Apennine watersheds. Within the geographic range, Rr is currently widespread in lakes and rivers (Gandolfi et al 1991;Bianco 1995), Sl inhabits small to medium premontane streams with Mediterranean water regimes (Kottelat & Freyhof 2007), and Tm is an obligate riverine of moderately cold running waters (Crivelli & Bianco 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is no record of roaches westward to this basin, while northward, typical PV district roach species are present, i.e., Leucos aula and Rutilus pigus , are not strictly related to Sarmarutilus (see Figure 2 ). The Magra-Vara basin has been geographically isolated since the late-Pliocene and early Pleistocene tectonic uplift of the surrounding mountains as follows [ 98 ]: (a) from the PV district by the northern Apennines, thus representing the northern border of most of the primary freshwater fish species native to Central Italy [ 99 ]; (b) from southern catchments by the Apuan Alps, a geographic barrier extending from the main Apennine to the sea which greatly effects the genetic structure of freshwater species [ 26 , 28 , 100 ]. In the early Pleistocene, when most of the current major southern basins such as Arno and Tiber were limited in extension due to marine introgression, Magra-Vara still had connections to both basins flowing in the Tyrrhenian Sea and the Adriatic Sea [ 98 ].…”
Section: Discussionmentioning
confidence: 99%